Cultural Genocide of Minorities in International Law: The Yazidi Community as a Model - Khalaf, Husam (Journal of Legal Sciences, 2026)
This community gained tragic global recognition after the genocidal attacks launched by ISIS against the Yazidis on August 3, 2014, particularly in the Sinjar region, which quickly turned into a targeted extermination campaign against the Yazidi population. Consequently, the date of August 3, 2014 entered the collective memory of the Yazidis as the seventy-fourth firman — an Ottoman Turkish term referring to comprehensive decrees issued by Ottoman rulers against the minorities of the empire. The Yazidis use this term to refer to the numerous massacres their community has suffered throughout the centuries. For a long time, the history of the Yazidis was insufficiently represented in academic scholarship. It is therefore important to understand why this people were targeted and to clarify how collective violence was perpetrated against them. Why were the Yazidis subjected to such violence? Was the 2014 genocide a rupture or rather a continuation of historical patterns? And what are the consequences of this genocide for the survivors nearly a decade after its commission?